Political Polarization and Societal Struggles in Pakistan: A Dialogic Exploration of Beckett’s Waiting for Godot - Shaikh, Tania Shabir; Afshan, Sahar (Journal of Research in Humanities, 2025)
Following qualitative research, the empirical study has engaged educators in an online inter-university dialogue to explore their perceptions of the socio-political realities of the contemporary world, with reference to the play Waiting for Godot. Participants were engaged in dialogue via Google Circles. Using Google Docs in groups, participants liaised digitally about the selected play, which is common across the curricula of public-sector universities across Pakistan. Since the present study engages educators in dialogue exchange, Bakhtin’s theory of Dialogism (1984) has guided this study. The collected data from participants’ written dialogic exchange transcripts via Google Circles was analyzed using the Thematic Analysis model, explicated by Saldana (2015). The key arguments based on the findings demonstrate that participants discussed and connected to the socio-political realities of contemporary Pakistan in the play, where both the literary plot and the real world reflect the state of hopeless waiting, dissatisfaction, and uncertainty. In both, power dominance is shaped by political polarization, socioeconomic inequalities, and systemic flaws. The findings are valuable for curriculum designers, literature instructors, and researchers in dialogic teaching as they provide significant insights into arguments for socio-political turbulent tides and their reflection in the literary world.